Software process improvement for small and medium enterprises techniques and case studies - Oktaba, Hanna; Piattini, Mario 1966- (Premier reference source, 2008)
"This book offers practical and useful guidelines, models, and techniques for improving software processes and products for small and medium enterprises, utilizing the authoritative, demonstrative tools of case studies and lessons learned to provide academics, scholars, and practitioners with an invaluable research source," - Provided by publisher